Angiography: in the shadow of a non-consensual Nobel - Janeiro, Catarina; Amarante, José Manuel; Andrade, José Paulo (Medicina Historica, 2025)
The most prolific period of medical research in Portugal, spanning approximately the 1930s to the 1960s of the 20th century, is often overshadowed by Moniz’s controversial Nobel Prize for his work on prefrontal leucotomy. Despite the importance of their contributions, the achievements of Portuguese researchers have not received proper recognition in the history of medicine. While Egas Moniz’s Nobel Prize for prefrontal leucotomy brought international attention to Portuguese medicine, it also eclipsed the pioneering work of the Porto School of Angiography. This article aims to systematically document the international impact of the Porto School, focusing on its network, innovations, and enduring influence on the field of radiology. This article aims to highlight the network of researchers and their impact on radiology, shedding light on their contributions to the international scientific community. systematically review and assess the international scientific impact of the Porto School of Angiography and its network of collaborators, highlighting their role in the development of radiology and vascular imaging. The study examines the international impact of the Porto School of Angiography from 1928 to 1970 through the work of investigators who collaborated with the Laboratory of Experimental Surgery based in Porto. We utilized three major databases—ISI Web of Science, Scopus, and Scimago—to select journals in the specific research fields of radiology, nuclear medicine, and imaging, and to track references to investigators from the School of Porto. Articles were accessed through PubMed, Google Scholar, or printed formats from online library resources. From a total of 44 documented collaborators, eight investigators were frequently cited as first authors in our timeline study. Sousa Pereira was the most cited author with his work on portography. The study also addresses challenges faced by the School, including language barriers, which may have affected its international recognition. This research not only sheds new light on the international impact of the Porto School of Angiography but also emphasizes the importance of accurate historical attribution in scientific achievements.